Improvement of foreign economic activity of «Planet of equipment» LLC (Economics and region, 2019)
At the present stage many Ukrainian enterprises are actively involved in foreign trade, which is important. However, the lack of experience or inexperience of domestic enterprises in foreign markets requires a lot of efforts to implement it. The article considers consumer foreign economic activity of enterprises, elaborates the main preconditions and general recommendations for improvement of foreign economic activity of enterprises.
Keywords: foreign economic activity; enterprise; import operations; mechanism of improvement; competitiveness; market segments